3D differentiation of bone-marrow derived mesenchymal stromal cells into the keratocyte lineage for corneal bioprinting - Taoum, Alexandre; Friede, Ronja; Thaden, Ole; Rachynskyi, Oleksandr; Frank, Andrea; Wang, Meng; Dehli, Friederike; Fuest, Matthias; Duarte Campos, Daniela Filipa (Advanced healthcare materials, 2025)
Corneal stromal keratocytes (CSK) play a critical role in maintaining corneal transparency and biomechanical integrity. However, challenges in obtaining enough functional CSK limit the progress of corneal tissue engineering and bioprinting. This study presents a novel protocol for the differentiation of bone marrow-derived mesenchymal stromal cells (BM-MSC) into CSK-like cells, optimized for both 2D and 3D culture systems, including 3D bioprinted constructs. A key innovation of this work is the preconditioning of BM-MSC on collagen-coated plates to reduce α-SMA expression, a marker associated with myofibroblast differentiation and fibrosis. Immunofluorescence and qPCR analyses demonstrated significant upregulation of CSK-specific markers, including Lumican, Keratocan, ALDH1A1, ALDH3A1, and Collagen I, while α-SMA expression remained undetectable. Notably, 3D cultures provided an enhanced environment for CSK differentiation, mimicking the corneal stroma more closely than 2D cell culture systems. The combination of preconditioning and 3D culture systems offers a promising approach for the biofabrication of functional corneal stroma, paving the way for future therapies aimed at treating corneal opacity and scarring.
Gesehen am 30.11.2025